A Study On The Effects Of High Energy Palm Oil Supplemented Diets On Broilers Growth Under Tropical Environment - Panja, Paichok (1991)

(untitled)
A series of experiments were conducted to study the effects of fat added high energy diets on the performance of broilers under the warm humid environment. Two types of fat namely palm oil and soybean oil, either singly or mixed , were incorporated in the test diets at varying levels (0 to 8%). Feeds were provided ad libitum and data on voluntary feed intake,growth rate , feed conversion and carcass com position were measured. Increasing palm oil level resulted in corresponding rise in the dietary energy concentrations, it was found that broilers fed on higher energy diets improved feed and energy consumption, daily weight gain and feed conversion ratio. Total carcass fat content was found to increase at higher levels of palm oil inclusions. When the level of protein was adjusted to maintain the calorie: protein ratio, the carcass fat content remained relatively constant regardless of palm oil levels added into the diets.Fatty acid com position in the body was found to be influenced greatly by dietary fat. When soybean oil was used instead of pal moil, the amount of linoleic and linolenic acids in the carcass was also increased proportionately. The results from these studies demonstrated the beneficiary effects of added fat high energy diets to broilers in the tropics. In spite of the adverse climatic conditions, the broilers especially those on high fat diet were able to sustain higher productivity in terms of growth rate and feed coversion ratio. This was only possible if the heat increment of broilers was reduced as a consequence of the presence of fat in the diet.